Studies on the Dehydration of Glycerol Over Niobium Catalysts - Lee, Young Yi; Moon, Dong Ju; Kim, Jong Ho; Park, Nam Cook; Kim, Young Chul (AMER SCIENTIFIC PUBLISHERS, 2011)
The dehydration of glycerol over nanosize niobium catalysts was conducted in a stainless steel autoclave reactor. The catalysts were prepared by the calcination of niobium oxalate between 200 and 700 degrees C. Catalysts were characterized by N-2 Physisorption, XRD and TPD of ammonia to investigate the effect of the calcination temperature and water on catalytic performance, catalysts' structures and acidity. Acrolein was mainly produced about 51-71% with useful by-products such as acetaldehyde and methanol. Amorphous Nb2O5 catalysts calcined at 200-400 degrees C significantly showed higher conversion of glycerol than the crystallized Nb2O5 catalyst calcined at 500-700 degrees C. Also the conversion of glycerol and selectivity of acrolein was increased with increasing the acidity of catalyst, which can be controlled by calcination temperature.
Keywords: GAS-PHASE DEHYDRATION; SUSTAINABLE PRODUCTION; ACROLEIN